Improving Fire Evacuation Routes: Non-Structural Barriers and Community Risk Perception - Anggun V. M. Anes; Dewi Larasati; Hanson E Kusuma; Lily Tambunan (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2026)
Highly populated areas are prone to fire hazards; hence, there is a need for proper evacuation routes. The high building density and limited access roads obstruct movement during emergencies. Most previous studies focused on structural barriers, while non-structural factors like community behavior, preparedness, and risk perception have received less attention. This paper will present an analysis of the impact of both evacuation barriers and community risk perception on recommended fire evacuation route improvements in highly populated areas. A sequential exploratory mixed-methods approach was used, with qualitative data from 111 respondents and quantitative data from 278 respondents analyzed through multivariate linear regression. The results indicate that non-structural barriers, preparedness levels, and community anxiety significantly influence recommendations for improving evacuation routes, while structural barriers have no effect. These findings confirm that behavioral and social barriers are more dominant than physical barriers in densely populated settlements. This study recommends improving risk literacy, conducting evacuation simulations, and establishing resident-based fire response teams to strengthen community-based mitigation.